Community Institutions with Nationalist Characteristics - Sinto Adi Prasetyorini (LEGAL BRIEF, 2023)
Nationalism is essentially a modern state ideology, like democracy and communism. Even colonialism and imperialism are forms of expansive nationalism. Nationalism is an awareness and pride in the state that creates attitudes and feelings that place greater importance on national life over personal, group, regional or party interests represented. This research is juridical normative. Using descriptive-analytical research specifications. Using secondary data collection sourced from library book materials, obtained through primary, secondary and tertiary legal materials. The normative analysis method as a way of discussing research material is based on all understandings in legal science. The results of the study show that Pancasila is understood not in its formula or status but in its contents, namely the noble values ??that are recognized as the agreed view of the nation's life. As attitudes and behaviours, it can be observed and assessed as to what our identity as a nation is like. In addition to the attitude and behaviour displayed. The characteristics possessed by civil society are such as living independently, having a high sense of tolerance, actively participating in all public policy formation, voluntary cooperation, upholding the values ??of justice and honesty, recognizing and respecting differences, and having strong national integrity. strong, upholding human rights and the rule of law as well as being open and transparent.